Isotope effects of ground and lowest lying vibrational states of H3-xDxO2- complexes - Ansari, Narjes; Meyer, Hans-Dieter (The journal of chemical physics, 2016)
Isotope effects of the H3O−23O2−3<msubsup>O2−</msubsup> anion are investigated. For this, the 24 lowest excited vibrational states of the H3−xDxO−23−xDxO2−3−xDx<msubsup>O2−</msubsup> complexes, with x = 0-3, are computed using two different Hamiltonians, namely, a 7D reduced-dimensionality one with a numerical representation of the kinetic energy operator (KEO) and a 9D full-dimensionality Hamiltonian with an exact analytic KEO. The computations are carried out with the multiconfiguration time-dependent Hartree method. The obtained results show that bridge and terminal H-D exchange cause a variation in energy with or without a rearrangement of states. A clear rearrangement of fundamental modes is observed in bridge H-D exchange of the H3O−23O2−3<msubsup>O2−</msubsup> complex, where the frequency of bridge hydrogen stretching (z) is strongly lowered by substitution. The isotope effects show that rotation (ϕ), rocking (u1 + u2), wagging (u1 − u2), and O-O stretch (R) modes are sensitive to terminal H-D exchange, while the bridge-atom bending (x,y) and stretch (z) modes are sensitive to bridge H-D exchange. An influence coefficient, which measures the influence of an excitation of one mode on the various 1D reduced densities, is defined and analyzed in detail. It is shown that the D3O−23O2−3<msubsup>O2−</msubsup> complex is more strongly correlated or coupled than the other isotopologues.